Rancang Bangun Kamus Digital Berbasis Chatbot Menggunakan Pendekatan Pattern Matching - Cahyo Prianto; Roni Andarsyah; Nisa Hanum Harani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The rapid development of technology today has had an impact on various fields of life, one of which is in the world of education. The application of information technology in the learning process at school or on campus has become commonplace. Smart devices such as smartphones connected to the internet can help the learning process and help encourage the communication process between educational stakeholders. In online learning, the process of communication and interaction between students and teachers switches through instant messaging providers. Taken from the 2019 digital report data issued by We Are Social Hotsuit, it is stated that the most popular instant messaging application in Indonesia is WhatsApp, where 83% of internet users in Indonesia are WhatsApp users, with this data making Indonesia one of the countries with the largest number of users in the world. Based on this, to support the performance of teachers in delivering learning materials, as well as provide faster access in searching for the required terms, this study built a digital chatbot-based dictionary that was embedded in the instant messaging application as the most popular message delivery medium in Indonesia. The process of building a chatbot-based digital dictionary in this study was carried out using the pattern matching method, which is a method included in the study of artificial intelligence that recognizes input from users to be matched with data stored in the database, and the appropriate response will be returned to the user. The subject content that is sampled in making this digital dictionary is physics. The result of this study is the existence of a chatbot-based digital dictionary that can assist students in finding definitions of various terms and formulas related to physics material, given by the teacher which students can access at any time as long as they are connected to the internet.